EVALUATION OF THE BIOLOGICAL ACTIVITIES OF THE ACETONE EXTRACT OF THE ROOTS OF SENNA ITALICA - Masoko, Peter; Gololo, Sechene; Mokgotho, Phineas; Eloff, Kobus; Howard, Rachmond; Mampuru, Leseilane (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Senna italica, a member of the Fabaceae family (subfamily Caesalpinaceae), is widely used traditionally to treat a number of disease conditions, such as sexually transmitted diseases and some forms of intestinal complications. The roots of Senna italica were collected from Zebediela subregion, Limpopo province (S.A), powdered and extracted with acetone by cold/shaking extraction method. The phytochemical composition of the extract was determined by thin layer chromatography (TLC). The chromatograms were visualised with vanillin-sulphuric acid and p-anisaldehyde reagents. The total phenolic content of the extract was determined by Folin-Ciocalteu method and expressed as TAE/g dry weight. The extract was assayed for the in vitro anticancer activity using Jurkat T cells, antioxidant activity using DPPH assay and antibacterial activity by bioautographic method and the microtiter plate method. The acetone extract of the roots of Senna italica inhibited the growth of Jurkat T cells in a dose- and time-dependent manner. The extract also possessed free radical scavenging activity as well as antibacterial activity against Pseudomonas aeruginosa, Enterococcus faecalis, Escherichia coli and Staphylococcus aureus. The biological activities observed in the acetone extract somewhat validated the ethnomedicinal use of Senna italica